JAK2 in Myeloproliferative Neoplasms: Still a Protagonist - Michael Stephan Bader; Sara Christina Meyer (MDPI AG, 2022)
The discovery of the activating V617F mutation in Janus kinase 2 (JAK2) has been decisive for the understanding of myeloproliferative neoplasms (MPN). Activated JAK2 signaling by JAK2, CALR, and MPL mutations has become a focus for the development of targeted therapies for patients with MPN. JAK2 inhibitors now represent a standard of clinical care for certain forms of MPN and offer important benefits for MPN patients. However, several key aspects remain unsolved regarding the targeted therapy of MPN with JAK2 inhibitors, such as reducing the MPN clone and how to avoid or overcome a loss of response. Here, we summarize the current knowledge on the structure and signaling of JAK2 as central elements of MPN pathogenesis and feature benefits and limitations of therapeutic JAK2 targeting in MPN.